Effect of distribution modulus (q) on the properties and microstructure development of a sustainable Ultra-High Performance Concrete (UHPC). (January 2022) - Wang, J.N.; Yu, R.; Ji, D.D.; Tang, L.W.; Yang, S.C.; Fan, D.Q.; Shui, Z.H.; Leng, Y.; Liu, K.N.
Abstract: This paper discusses the effect of distribution modulus ( q ) on the properties and microstructure development of a sustainable Ultra-High Performance Concrete (UHPC) incorporating gold tailings. To be specific, the Modified Andreasen and Andersen (MAA) model is used to design the UHPC matrix, in which a previously seldom focused value — distribution modulus ( q ) is carefully investigated here. The deviation between experimental mixtures and different target curves (with different q ) are concluded based on Weighted Residual Sum of Squares (WRSS). Then, the fresh and hardened behaviors of the developed UHPCs with different q value are evaluated. The obtained experimental results show that the declination of q can increase the wet packing density of UHPC. Besides, when the distribution modulus ( q ) is controlled in the range of 0.17–0.19, a sustainable UHPC with advanced properties and microstructure can be produced. For instance, the compressive strength of the optimum UHPC matrix in this study can reach about 136.2 MPa after curing in standard condition for 28 days. This implies that the normally selected distribution modulus ( q ) value – 0.23 can not always guarantee the maximum packing density and best characteristics for UHPC matrix.